2018
DOI: 10.1089/brain.2017.0538
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Brain Connectivity in a Large Study of Huntington's Disease Gene Mutation Carriers and Healthy Controls

Abstract: Huntington's disease (HD) is an inherited brain disorder characterized by progressive motor, cognitive, and behavioral dysfunctions. It is caused by abnormally large trinucleotide cytosine-adenine-guanine (CAG) repeat expansions on exon 1 of the Huntingtin gene. CAG repeat length (CAG-RL) inversely correlates with an earlier age of onset. Region-based studies have shown that HD gene mutation carrier (HDgmc) individuals (CAG-RL ≥36) present functional connectivity alterations in subcortical (SC) and default mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 63 publications
3
26
0
Order By: Relevance
“…In addition, the volumetric analysis identified overlapping significant decreases in these same areas; however, it also showed a significant decrease in the lateral, medial and inferior orbitofrontal cortex (bilaterally) as has been reported previously in structural and diffusion studies (Matsui et al, ; Nopoulos et al, ). Moreover, our structural results are consistent with pronounced decrease of functional markers in the frontoparietal and temporo‐occipital cortex in HD (Espinoza et al, ; Feigin et al, ; Kuwert et al, ; Poudel, Stout, et al, ; Wolf et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the volumetric analysis identified overlapping significant decreases in these same areas; however, it also showed a significant decrease in the lateral, medial and inferior orbitofrontal cortex (bilaterally) as has been reported previously in structural and diffusion studies (Matsui et al, ; Nopoulos et al, ). Moreover, our structural results are consistent with pronounced decrease of functional markers in the frontoparietal and temporo‐occipital cortex in HD (Espinoza et al, ; Feigin et al, ; Kuwert et al, ; Poudel, Stout, et al, ; Wolf et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…Correlations between functional connectivity and disease burden confirmed the involvement of VIS and cortical‐cerebellar motor networks in the whole HD spectrum (Espinoza et al, ; Koenig et al, ; Wolf, Sambataro, Vasic, Baldas, et al, ; Wolf et al, ).…”
Section: Resultsmentioning
confidence: 79%
“…However, two different studies, investigating long range coupling activity between functional networks in pre‐HD, showed reduced connectivity between salience network and several networks. Espinoza et al () reported reduced connectivity between insula and subcortical structures related with increasing CAG repeat length. Similarly, Mason and associates (2018) revealed that in pre‐HD participants the majority of the significant hypoconnectivity connections included the salience network.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed decreasing connectivity with increasing CAG repeat length in the putamen network, and between the putamen and insular cortex. CAG repeat length was also positively associated with functional connectivity between calcarine and middle frontal gyri networks but negatively associated with connectivity between other visual networks, indicating a complex genetic effect on posterior connectivity (Espinoza et al, ).…”
Section: Introductionmentioning
confidence: 99%